Dimethyl sulfoxide pivaloyl chloride: a new reagent for oxidation of alcohols to carbonyls - Dubey, Abhishek; Kandula, Subba Rao V.; Kumar, Pradeep (Synthetic Communications, 2008)
An efficient procedure for conversion of alcohols to the corresponding carbonyl compounds, an alternative to the classical Swern oxidation, is described. Pivaloyl chloride is employed as a mild and inexpensive electrophile. A possible reaction mechanism is proposed.
Keywords: Alcohols; carbonyls; DMSO; pivaloyl chloride; Swern oxidation

Beyond hydrofunctionalisation: a well-defined calcium compound catalysed mild and efficient carbonyl cyanosilylation - Yadav, Sandeep; Dixit, Ruchi; Vanka, Kumar; Sen, Sakya S. (Chemistry-A European Journal, 2018)
Organocalcium compounds have been reported as efficient catalysts for various transformations, for cases in which one of the substrates contained an E-H (E=B, N, Si, P) bond. Here, we look at the possibility of employing an organocalcium compound for a transformation in which none of the precursors has a polar E-H bond. This study demonstrates the utilization of a well-defined amidinatocalcium iodide, [PhC(NiPr)(2)CaI] (1) for cyanosilylation of a variety of aldehydes and ketones with Me3SiCN under ambient conditions without the need of any co-catalyst. The reaction mechanism involves a weak adduct formation between 1 and Me3SiCN leading to the activation of the Si-C bond, which subsequently undergoes sigma-bond metathesis with a C=O moiety. Such a mechanistic pathway is unprecedented in alkaline earth metal chemistry. Experimental and computational studies support the mechanism.
Keywords: Ca catalysis; carbonyls; cyanosilylation; Density functional calculations; transition-metal free